Heretability and Correlation of Vegetative and Generative Character on Genotypes of Jatropha (Jatropha curcas Linn.). (2015) - Maftuchah,; Reswari, Helvi Ardana; Ishartati, Erny; Zainudin, Agus; Sudarmo, Hadi
Abstract: This study was aimed to obtain information of heritability predictive value and correlations of vegetative and generative characters on six genotypes of J. curcas . The characters of plant height, leaf number, leaf width, number of primary and secondary branches, number of fruit bunches, number of fruits per plant, seed's and 100 seeds' dry weight showed high predictive value of heritability. Characters related to positive correlation and high heritability values (leaf width, number of primary branches, number of secondary branches, number of fruit bunches, number of fruits per plant) are able to be used as criteria for selection of J. curcas plant.